Nitrofurantoin inhibits contractions of myometrium isolated from pregnant and nonpregnant rats - Kavak, Ebru Celik; Kacar, Emine; Kavak, Salih Burçin; Bulmuş, Özgür (My University, 2018)
We aimed to investigate the effects of nitrofurantoin, a commonly used antibiotic for urinary tract infections, on spontaneous contractions of rat myometrium isolated from 16-day pregnant and nonpregnant rats. Myometrial strips were suspended in a standard organ bath and after the manifestation of spontaneous contractions under 1 g of resting tension, nitrofurantoin was applied to the organ bath as 50, 250 and 500 µM doses. Amplitude and frequency of contractions were recorded for 20 minutes before and after application of the drug. The bath was washed to remove the drug from the medium after recording the effect of each dose and the contractions were enrolled again to show the reversible effect of the drug. The effects of nitrofurantoin on amplitude (milligrams) and frequency of spontaneous contractions were evaluated. Data were statistically analyzed using the Student’s t test and p<0.05 was considered to be statistically significant. Nitrofurantoin inhibited spontaneous contractions in a dose dependent manner. Although both the frequency and amplitude of contractions were significantly inhibited at all doses, the inhibition of contractions were 100% at 500 µM dose, which corresponds to the dose used for prophylaxis in clinical practice. The results of this in vitro study indicated that nitrofurantoin inhibits spontaneous contractions of myometrium isolated from pregnant and nonpregnant rats.
Keywords: Fizyoloji